An observational study of the reliability and concurrent validity of heart rate variability devices in athletes - Johansson, H.; Adderley, E.; Clarke, S.; McIntyre, P.; Reilly, G.; Caulfield, B.; Holden, S. (Frontiers in Physiology, 2025)
Background: Heart rate variability (HRV) is a non-invasive indicator of autonomic nervous system function and is increasingly used in athlete monitoring. While electrocardiography (ECG) is the gold standard for HRV measurement, its use is limited in field settings.